Economic impact assessment of alternative climate policy strategies - Claudia Kemfert (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper investigates the world economic implications of climate change policy strategies, especially the evaluation of impacts by an implementation of Clean Development Mechanisms, Joint Implementation and Emissions trading with a world integrated assessment model. Of special interest in this context are the welfare spill over and competitiveness effects that result from diverse climate policy strategies. In particular, this study elaborates and compares multi gas policy strategies and explores the impacts of the inclusion of sinks. Because of the recent decision of an isolated climate policy strategy by the United States of America, we examine the economic impacts of all world regions by a non cooperative and free rider position of the USA. It turns out that Clean Development Mechanisms and Joint Implementation show evidence of improvement in the economic development in the host countries and increase the share of new applied technologies. The decomposition of welfare effects demonstrates that the competitiveness effect including the spill over effects from trade have the strongest importance because of the intense trade relations between countries. Climatic effects have a significant impact within the next 50 years, cause considerable welfare losses to world regions and will intensify if some highly responsible nations like the USA do not reduce their emissions.
Keywords: C0; D5; Q0; 330; Impacts of climate change; integrated assessment modelling; Klimaschutz; Emissionshandel; Umweltabkommen; Wirkungsanalyse; Wohlfahrtsanalyse; Welt